The spatiotemporal evolution of toponymic cultural landscapes in Hebei Province, China, and its influencing factors - Da Zhang; Han Song; Pingzhi Li; Yixi Guo; Yating Luo; Sheng Mao; Zijia Feng; Shuwen Zheng; Zhuoyan Jiang (PLoS ONE, 2026)
Current research on toponymic cultural landscapes lacks systematic attention to geographical transition zones and often neglects the interpretation of long-term evolutionary processes and driving mechanisms. This study examines 1,854 township-level place names in Hebei Province, China, by integrating methods such as kernel density estimation, geographic detectors, and spatial autocorrelation analysis. Focusing on the transition zone along the Taihang Mountains–Great Wall corridor, patterns of spatiotemporal differentiation and the dual mechanisms shaping changes in place names are investigated. The findings reveal significant spatiotemporal variation in Hebei’s place names. Natural environment names have contracted toward northeastern mountainous and coastal regions, while cultural names have shifted northward. The transition zone exhibited a “military-to-civilian” transformation characteristic during the Ming and Qing dynasties. Slope gradient and vegetation coverage are identified as primary natural drivers, whereas ethnic integration and migration during the Ming Dynasty constitute the key social factors. This study enriches interdisciplinary research on human–land relationships and toponymic landscapes in transition zones, proposes region-specific conservation strategies, and provides a scientific basis for the protection of toponymic cultural heritage in similar transition zones across Hebei and North China.